Tingkat Kinerja Penyuluh Pertanian di BAPPELUH Kota Kendari Sulawesi Tenggara. - Abdullah, Sukmawati (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
This research has been done on March until April 2010, aims to know the distribution of agriculture extension agent on the observed characteristic, determine the performance level of agriculture extension agent and determine factors which related to agriculture extension performance in BAPPELUH Kendari City. The population of this research is all of the extension agent (PPL) under the supervision of BAPPELUH in some BPP Sub District Kendari City. Sampling is done through the census, which all of the population became the research objects so that a total of respondents on this research is 45. Data that has been collected came from the tabulation analysis according to the necessity, then counted with the presentation. Then, to know the performance level of agriculture extension agent used the Burhan’s formula (2000), that is I=J/K. Meanwhile, to know the factors related to agriculture extension agent performance in BAPPELUH Kendari City, it used the Rank Spearman analysis. The result of the research shows that majority of the agriculture extension agent is on productive age, has a high education level, that is S1 and S2, has a good experience on the establishment, a good income to support his job, supported by transportation and in a high-level cosmopolite. The level of agriculture extension agent performance belongs to high with 75,56%. Age, education level, income, transportation ownership, and the cosmopolite factors are related significantly to the agriculture instructor, meanwhile, the experience of establishment doesn’t have a significant relation to the agriculture extension agent performance in BAPPELUH Kendari City.